A model of agricultural origins. (July 2018) - Piperno, Dolores
Agriculture is one of the key innovations of human societies, yet the nature of and reasons for its emergence are debated. A new model that hindcasts past global population suggests that an improving climate increased plant productivity and human population density, facilitating domestication.